Monitoring dan Analisis QoS Jaringan Wireless LAN di Gedung Harni Koesno: Studi Kasus dengan Wireshark dan Thiphone - slamet purwo santosa; ahmad tajuddin (JURNAL ELEKTRO, 2026)
This study examines the quality of the Wireless LAN (WLAN) network at Harni Koesno Building, Department of Midwifery, Poltekkes Kemenkes Jakarta III, focusing on Quality of Service (QoS) analysis. The aim is to measure and evaluate WLAN QoS performance through aspects such as delay, bandwidth, jitter, and packet loss. Data collection techniques included direct observation, network analysis software and user surveys. The results show a delay of 22.22 ms, 0% packet loss, and 68.70 ms jitter, all categorized as "Excellent" according to Telecommunication and Internet Protocol Harmonization Over Networks (TIPHON) standards. This study aims to offer an overview of QoS of the WLAN network in Harni Koesno Building and propose recommendations for network performance improvements, with the goal of enhancing user satisfaction within the Poltekkes environment, particularly in Harni Koesno Building.